DIMENSI SERAT DAN KOMPOSISI KIMIA KAYU ALPOKAT - Yacob Ando (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The fiber dimension and chemical composition of Persea sp. are presented in this report. The analyses include determination of the fiber dimension (length, diameter cell wall thickness, and Runkel ratio), and chemical composition. (cellulose, lignin, pentosan, ash, extractives, and solubility in one percent sodium hydroxide solution).The study reveals that the average fiber length is 1105.36 µ, diameter 19. 09 µ, cell wall thickness 2,36 µ and Runkel ratio 0.37. The cellulose content amounts to 45.46 percent, lignin 23.71 per cent, pentosan 19.67 percent and ash 1.27 percent.The solubility in cold water ; was found to be 5.43 percent; in hot water 5.55 percent, in alcohol benzene 1:2 ratio, 4.02 percent and in one per cent sodiumhydroxide solution 11.36 percent.Based on the fiber dimension and the chemical composition, it was found that Persea wood is suitable for producing good quality paper.